Green supply chain management: an empirical investigation on the construction sector - Balasubramanian, Sreejith; Shukla, Vinaya (Supply chain management, 2017)
Purpose Curtailing the adverse environmental impacts of the construction sector is one the major challenges of the twenty-first century. However, despite the significance of this problem, the limited efforts so far to tackle the negative impacts associated with this particular sector have been largely fragmented and disjointed. Given that the net green outcome of a construction project is the sum total of the efforts undertaken at the various supply chain stages (from the initial design to the end-of-life demolition) by different stakeholders, the green supply chain management (GSCM) approach is seen as a way forward toward streamlining the fragmented efforts at greening the sector. This forms the motivation of the present work, and this paper aims to develop, validate and apply a multi-dimensional GSCM framework for the construction sector. Design/methodology/approach A comprehensive GSCM assessment framework consisting of nine constructs (external and internal drivers; external and internal barriers; core and facilitating GSCM practices; economic, environmental and organizational performance implications) and their underlying factors was developed through an extensive literature review. Using data collected through a structured questionnaire, the framework was validated, and the relevance/appropriateness of each construct and its underlying factors, along with the hypothesized relationships between the constructs, were assessed separately for each supply chain stakeholder. Findings The findings confirm the validity and reliability of the constructs and their underlying factors as well as the assessment framework. In general, the implementation of green practices has had a positive impact on the environmental, economic and organizational performance for all stakeholders, while the extent of the green practices implemented depends on the relative strength of the drivers and barriers. Research limitations/implications This study fills a gap in the literature about applying/implementing GSCM in the construction sector. Practical implications The findings provide practitioners, policy makers and organizations associated with the UAE construction sector, as well as the construction sector in general, insight into all key aspects of GSCM. Originality/value A comprehensive survey-based assessment of GSCM for the construction sector has not been previously attempted and constitutes the novelty of this work.